Children's processing of emotions expressed by peers and adults: an fMRI study - Höhl, Stefanie; Brauer, Jens; Brasse, Gabriele; Striano, Tricia; Friederici, Angela D. (Social neuroscience, 2010)
The recognition of emotional expressions is an important skill and relates to social functioning and adjustment in childhood. The current functional MRI study investigated the neural processing of angry and happy facial expressions in 5- to 6-year-old children and in adults. Participants were presented happy and angry faces of adults and children while they performed a non-emotion-related task with low cognitive load. Very similar neural networks were involved in the processing of angry and happy faces in adults and children, including the amygdala and prefrontal areas. In general, children showed heightened amygdala activation in response to emotional faces relative to adults. While children showed stronger amygdala activation in response to angry adult compared to angry child faces, adults showed stronger amygdala activation for angry child faces. In both age groups enhanced amygdala involvement was found for happy peer faces relative to happy non-peer faces, though this effect was only a tendency in adults. The findings are discussed in the context of the development of the social brain network.